Simplified watermarking scheme for sensor networks. (12th April 2010) - Kamel, Ibrahim; Juma, Hussam
Wireless sensor networks (WSNs) are used in a variety of applications including military, environmental, and smart spaces. These applications might deal with sensitive information like enemy movements in the battlefield. Sensors are susceptible to various types of attack, such as data modification, data insertion and deletion, or even physical capture and sensor replacement. Therefore, checking the integrity of the transmitted data is critical for WSNs' applications. The inherited constraints in WSNs, e.g., computational capability and limited energy resources, pose extra challenges for providing data security. This makes traditional security techniques, which are based on data encryption, not suitable for WSNs. This paper focuses on the integrity of sensor data in WSNs. Motivated by the work of Guo et al. (2007) we propose a fragile watermarking technique, called light weight chained watermark (LWC watermark), to detect unauthorised data alterations. Watermarking techniques are usually computationally lightweight and do not require much memory resources. We provide detailed security analysis of the proposed LWC watermark and compare it with a recent work of Guo et al. (2007) for watermarking data streams. While the robustness of LWC is similar to that of Guo et al. (2007), LWC offers significant performance improvement. We implemented both techniques (the proposed LWC and Guo et al., 2007) and performed extensive performance experiments. The experimental results on synthetic sensor data streams prove that the proposed LWC watermarking scheme is much faster than Guo et al. (2007) watermarking technique. This makes the proposed schemes more suitable for wireless sensor network environment where computing and power resources are very limited.